PBK/TOPK expression in non‐small‐cell lung cancer: its correlation and prognostic significance with Ki67 and p53 expression. Issue 5 (11th September 2013) - Lei, Bin; Liu, Shuguang; Qi, Wenjuan; Zhao, Yunfei; Li, Yumei; Lin, Ni; Xu, Xiaoyan; Zhi, Chen; Mei, Juanjuan; Yan, Zhimin; Wan, Liyan; Shen, Hong
<x xml:space="preserve">Abstract</x> Aims The aim of this study was to evaluate the prevalence of PBK/TOPK (PDZ‐binding kinase/T‐LAK cell‐originated protein kinase) expression, and explore the prognostic significance of PBK/TOPK expression alone and in combination with Ki67 and p53 expression in non‐small‐cell lung cancer (NSCLC). Methods and results We detected PBK/TOPK expression in 30 samples of normal lung tissue, 32 lymph node metastases and 279 primary non‐small‐cell lung cancers by immunohistochemistry, and analysed the correlation of PBK/TOPK expression with Ki67 and p53 expression in primary tumour tissues. The results showed that PBK/TOPK expression was higher in lymph node metastases (75%) than in primary tumours (44.8%) and normal lung tissues (0%). PBK/TOPK expression was associated with histological type, lymph node metastasis, and TNM stage, and was positively correlated with Ki67 and p53 expression in NSCLC. Univariate and multivariate survival analyses showed that PBK/TOPK expression was significantly associated with an unfavourable prognosis in NSCLC. The prognosis of patients with tumours positive for both PBK/TOPK expression and Ki67 or p53 expression was also significantly unfavourable. Conclusions PBK/TOPK expression is positively correlated with Ki67 and p53 expression, and can be used as an independent prognostic factor in NSCLC.